Vzgojno-izobraževalne vsebine geografije naselij - Drozg, Vladimir (Geografski vestnik, 2000)
The article is an attempt to determine which topics from the geography of settlement are suitable for inclusion in the geography curriculum and what is their educational significance. The selection is based on geographical subject matter and the number of educational objectives included in each individual topic.
Keywords: naselja; geografija naselij; pouk; metodika pouka; didactic method; didaktika